Analyzing Genre of Character-Describing Cards in ‘Clash Royale’ Android Game - Kurniawan, Muhammad Hafiz (Universitas Ahmad Dahlan, 2020)
Playing games is the most enjoyable activity for some teenagers. However, playing games nowadays can be considered both a wasting time activity because by playing games some of teenagers spend much time playing it and an addicting activity making the players anti-social persons because they tend to isolate them from their surroundings while playing. However, some android games can offer the good example as the learning materials for Discourse Analysis course. One of those is the game from Supercell ‘Clash Royale’ which is considered the famous games which most game players have ever played. The unique way of describing the game characters through the cards is the object of this analysis. The method of collecting the data of these games is by capturing the pictures of the Clash Royale games and other similar games using the screenshot feature which is available in smartphone. After capturing the pictures, they are transcribed into text and analyze them by comparing the way in describing the characters in the cards. The pictures are used to compare the structure of cards which are used to describe the game characters. The use of bending and blending genre which appear in describing the characters is used to arouse the humorous feeling among the game players without breaking the conventional structure of the genre.